The Influence of Specialization, Independence, and Public Accounting Firm Size on Audit Quality with Auditor Integrity as a Moderating Variable - Elisa, Anna; Iskak, Jamaludin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2025)
Audit quality is a crucial aspect of financial transparency and corporate accountability. This study examines the influence of public accounting firm (PAF) specialization, independence, and firm size on audit quality, with auditor integrity as a moderating variable. Using agency theory and professionalism theory as theoretical frameworks, this study explores how these factors contribute to the reliability of financial audits. The findings indicate that specialization and independence have a significant positive impact on audit quality, whereas firm size alone does not necessarily guarantee higher audit quality. Moreover, auditor integrity enhances the relationship between independence and audit quality, reinforcing the importance of ethical standards in the auditing profession.